Embedded software verification and debugging - Lettnin, Djones; Winterholer, Markus (Springer, 2017)
This book provides comprehensive coverage of verification and debugging techniques for the embedded software frequently used in safety-critical applications (e.g., automotive), where failures are unacceptable. It also discusses emerging trends and techniques.- Resumé vydavatel
Keywords: vestavěné systémy; software; počítačové programy; ladění softwaru; formální verifikace; embedded systems; computer program; software debugging; formal verification; elektronické knihy; sborníky; electronic books; papers of several authors